Challenges in the migration to 4G mobile systems. - Hui, Suk Yu
With the rapid development of wireless communication networks, it is expected that fourth-generation mobile systems will be launched within decades. 4G mobile systems focus on seamlessly integrating the existing wireless technologies including GSM, wireless LAN, and Bluetooth. This contrasts with 3G, which merely focuses on developing new standards and hardware. 4G systems supports comprehensive and personalized services, providing stable system performance and quality service. However, migrating current systems to 4G presents enormous challenges. In this article, these challenges are discussed under the headings of mobile station system, and service aspects. Proposed solutions to the research problems in each aspect are also examined.
Keywords: 4G mobile systems; Bluetooth; GSM; Mobile station system; Personalized services; Quality service; Stable system performance; Wireless LAN; Wireless communication networks; Wireless technologies